(untitled) (Medical Forum Monthly, 2021)
: To find out the impact of nurse-led self-management support interventions on quality of life among kidney transplant patients. Study Design: Qausi experimental study Place and Duration of Study: This study was conducted at the Rukhsana Akhtar Bahria International Orchard Hospital Lahore, Pakistan from June, 2021 to October, 2021 for a period of 05 months. Materials and Methods: Thirty-six patients were selected by using purposive sampling technique. After taking informed consent all kidney transplant patients aged between 18 years to 60 years, visited the post-transplantation OPD and continuously in follow-up sessions were included. Results: The mean age was 31.44±9.31 with 55.6% females. 27.8% can read/write and 52.8% belongs to urban area. 69.44% of donors were non-relatives. There was significant difference in the KDQOL before and after 4 month intervention. Over all their general health remain same after transplantation (p>0.05) but there physical function, emotional function, social function, daily activities and physical and emotional problems showed significant difference after intervention (p <0.05). 11.1% participants were having excellent quality of life and but after intervention it has increased to 44.4% (p<0.05). Conclusion: Nurse led self-management program had significant impact on increasing the quality of life of kidney transplant patients. Nurses are the important factor for educating patients which can lead to significant change in their behavior and quality of life as well.